Metabolismo de carboidratos não-estruturais em ruminantes - Cañizares, G. I L [UNESP]; Rodrigues, L. [UNESP]; Cañizares, M. C. [UNESP] (My University, 2009)
The carbohydrates provide 50 to 80% of the dry matter of grain and roughage and can be divided into structural (cellulose, hemicellulose) and non-structural (starch, pectin and sugars). The non-structural carbohydrates are primarily digested in the rumen and its dynamic process is a sequence for the supply of nutrients to the intestine. The quality and quantity of products resulting from ruminal fermentation are dependent on the type and activity of microorganisms in the rumen influenced by the type of food processing and that are subject of cereal grains that make up the diet. The NSC escape of rumen fermentation to be digested into glucose in the small intestine by pancreatic enzymes of origin (α-amylase) and intestinal mucosa (maltase and isomaltase). Starch is the most important energy supplier of cereals, which are important components of diets for intensive production of milk and meat.
Metabolism of non-structural carbohydrates in ruminants
Keywords: Carbohydrates digestion; Glucose; Pectin; Ruminal fermentation; Starch; Bovidae